Majlis al-‘Ulama’ al-Indūnīsī fī Munādalat al-Barnāmij al-Siyāsī - Suwito, Suwito; Wahab, Muhbib Abdul (Studia Islamika, 1995)
The birth of the Indonesian Ulema Council (MUI), among others, initiated by the New Order. Minister of Religion formed the Indonesian Islamic Propagation Center (WWII) in charge of organizing workshop preachers in Indonesia on 26-29 November 1974. Among the results of the workshop consensus is forming MUI.The initiative was in addition to the presence of concerned government organizations 'scholars' to accelerate the implementation of its discretion, as well as outside of Islam similar associations have been formed. General Assembly of the Indonesian Bishops (MAWI) for the Ummah Catholics had formed in 1924 and the Communion of Churches in Indonesia (PGI) for the Ummah Protestant founded in 1950.DOI: 10.15408/sdi.v2i4.823